Pulsed electric field application reduces carbapenem- and colistin-resistant microbiota and blaKPC spread in urban wastewater. (1st July 2020) - Ballash, Gregory A.; Lee, Seungjun; Mollenkopf, Dixie F.; Mathys, Dimitria A.; Albers, Amy L.; Sechrist, Emily; Feicht, Sydnee M.; Van Balen Rubio, Joanny C.; Sullivan, S. Mažeika P.; Lee, Jiyoung; Wittum, Thomas E.
Abstract: Wastewater flows from metropolitan areas, especially those with healthcare inputs, can serve as transport reservoirs for the dissemination of clinically-relevant antimicrobial resistant bacteria (ARB) such as carbapenem- (CR) and colistin-resistant (CoR) strains. Pulsed electric field (PEF) is an emerging wastewater management tool for reducing bacterial loads without generating environmentally harmful byproducts, but it's ability to reduce ARB and their genetic determinants is not well reported. We collected 86, 10-L raw wastewater influent samples from a large metropolitan wastewater treatment plant in Columbus, Ohio and subjected them to low (34 kV cm −1 for 67 μsec) and high (36 kV cm −1 for 89 μsec) PEF treatment. We quantified the PEF effectiveness by measuring concentrations of total coliform bacteria, CR and CoR bacteria, and the epidemic carbapenemase gene, bla KPC, before and after PEF treatment. Utilizing marginal linear regression models with generalized estimating equations, we observed that low and high PEF treatment resulted in a 1.94 (95% CI 2.06–1.81; P < 0.001) and 2.32 (95% CI 2.46–2.18; P < 0.001) log reduction of total coliform bacteria concentrations, respectively. Low and high PEF treatment produced similar log reductions between CR E. coli (2.01 (95% CI 2.15–1.86; P < 0.001); 2.14 (95% CI: 5.30–4.61; P < 0.001)) and CR Enterobacteriaceae concentrations (1.55 (95% CI 1.70–1.41; P < 0.001); 1.86 (95% CI 2.05–1.68; P < 0.001)), and resulted in a 1.15 log (95% CI 1.38–0.93, P < 0.001) and 1.28 log (95% CI 1.54–1.03, P < 0.001) reduction of absolute bla KPC concentrations. Log CoR E. coli concentrations were reduced by 2.47 (95% CI 2.78–2.15; P < 0.001) and 2.52 (95% CI 2.91–2.15; P < 0.001) and CoR Enterobacteriaceae by 2.24 (95% CI 2.52–1.95; P < 0.001) and 2.50 (95% CI 2.89–2.11; P < 0.001) following low and high PEF application. PEF can be applied for wastewater management as an independent treatment method, particularly at critical control points, such as an on-site management of wastewater from hospitals or other healthcare facilities, or in series with other conventional methods to reduce total bacterial loads and concentrations of clinically-relevant ARB. Highlights: Application of PEF reduced carbapenem- and colistin-resistant bacteria in wastewater. Epidemic carbapenemase gene concentrations decreased after wastewater PEF application. Wastewater chemistry parameters marginally impacted PEF efficacy. PEF treatment of high-risk influent may mitigate environmental spread of antimicrobial resistance.